Long-term variability of oceanographic–meteorological parameters in Banyuwangi waters, Indonesia, related to ENSO and the IOD - Putri, Devi Amelia Eka; Zakky, Muhammad; Sawiji, Asri; Santoso, Eko Hadi (Journal of Marine Resources and Coastal Management, 2026)
Oceanographic and meteorological parameters in tropical coastal waters are highly dynamic and strongly influenced by large-scale climate variability, particularly the El Niño–Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD). As global climate change intensifies atmospheric and oceanic variability, Indonesia’s coastal regions, including Banyuwangi waters, become increasingly vulnerable to environmental fluctuations. This study aims to analyze long-term trends and anomalies of oceanographic–meteorological parameters during 2015–2024 and evaluate their relationships with ENSO and IOD variability. The analyzed parameters included wind speed, significant wave height, surface current velocity, tides, rainfall, sea surface temperature (SST), and chlorophyll-a concentration. Linear regression was applied to identify long-term trends, while Spearman’s rank correlation analysis was used to assess relationships between climate indices and environmental parameters. The results indicate increasing trends in wind speed (6.47–6.76 knots), significant wave height (0.867–0.901 m), surface current velocity (8.18–8.65 cm s⁻¹), and tidal height (10.00–10.04 cm), whereas rainfall exhibited a decreasing trend from 6.14 mm to 4.88 mm during the study period. Correlation analysis revealed that ENSO and IOD exerted variable influences on rainfall, SST, and chlorophyll-a concentration, with significant correlations occurring only during specific years. ENSO showed a strong positive relationship with rainfall in 2023 (ρ = 0.704), while IOD exhibited a significant negative relationship with rainfall in 2015 (ρ = −0.666). Significant relationships were also identified between climate indices and SST as well as chlorophyll-a concentration, indicating that regional oceanographic conditions respond to both large-scale climate forcing and local environmental factors. Overall, the findings demonstrate that the impacts of ENSO and IOD on Banyuwangi waters are dynamic and temporally variable, emphasizing the importance of long-term monitoring to support coastal resource management and climate adaptation strategies.